BAYESIAN BASED BRAIN SOURCE LOCALIZATION TECHNIQUE USING EEG SIGNALS - JATOI, MUNSIF ALI (2016)
Brain Source localization from EEG/MEG is an ill-posed inverse problem with high uncertainty in the solution. This source localization information is used to diagnose various brain disorders such as epilepsy, schizophrenia, stress, depression and Alzheimer.